From small aromatic molecules to functional nanostructured carbon by pulsed laser-induced photochemical stitching - Gokhale, R. R.; Thakare, V. P.; Warule, S.; Lefez, Benoit; Hannoyer, Beatrice; Jog, Jyoti Prakash; Ogale, S. B. (AIP Advances, 2012)
A novel route employing UV laser pulses (KrF Excimer, 248 nm) to cleave small aromatic molecules and stitch the generated free radicals into functional nanostructured forms of carbon is introduced. The process differs distinctly from any strategies wherein the aromatic rings are broken in the primary process. It is demonstrated that this pulsed laser-induced photochemical stitching (PLPS) process when applied to routine laboratory solvents (or toxic chemical wastes when discarded) Chlorobenzene and o-Dichlorobenzene yields Carbon Nanospheres (CNSs) comprising of graphene-like sheets assembled in onion-like configurations. This room temperature process implemented under normal laboratory conditions is versatile and clearly applicable to the whole family of haloaromatic compounds without and with additions of precursors or other nanomaterials. We further bring out its applicability for synthesis of metal-oxide based carbon nanocomposites. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4721268]